2022
DOI: 10.1001/jamainternmed.2022.0184
|View full text |Cite
|
Sign up to set email alerts
|

US Food and Drug Administration–Mandated Postmarketing Studies for High-risk Cardiovascular Devices Approved 2015-2019

Abstract: 55 to 70 years) to discuss screening risks and benefits with their physician, many US cancer centers (26%) recommend that all men universally receive PSA screening (using language such as "annual prostate screening is recommended for men beginning at age 50 years"), without advising shared decisionmaking. Most centers (62%) do not discuss screening risks on their websites.A limitation of this study is that the public recommendations of cancer centers may not reflect their clinical practices. Nevertheless, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Breakthrough devices have been shown to have evidence of low quality, with most high-risk therapeutic breakthrough devices supported by a single, small study and sometimes no effectiveness end points . Disappointingly, postmarket studies for devices are usually neither rigorous nor completed in a timely manner . Use of the “breakthrough” terminology is potentially deceiving to both patients and physicians; research has shown this terminology gives the false impression that a medical product is more effective than the evidence has actually demonstrated …”
Section: Fda Approvalmentioning
confidence: 99%
See 1 more Smart Citation
“…Breakthrough devices have been shown to have evidence of low quality, with most high-risk therapeutic breakthrough devices supported by a single, small study and sometimes no effectiveness end points . Disappointingly, postmarket studies for devices are usually neither rigorous nor completed in a timely manner . Use of the “breakthrough” terminology is potentially deceiving to both patients and physicians; research has shown this terminology gives the false impression that a medical product is more effective than the evidence has actually demonstrated …”
Section: Fda Approvalmentioning
confidence: 99%
“…22 Disappointingly, postmarket studies for devices are usually neither rigorous nor completed in a timely manner. 23 Use of the "breakthrough" terminology is potentially deceiving to both patients and physicians; research has shown this terminology gives the false impression that a medical product is more effective than the evidence has actually demonstrated. 24,25…”
Section: Fda Approvalmentioning
confidence: 99%
“…Later investigations demonstrated increased morbidity and mortality, largely owing to cardiotoxicity associated with HCQ. The FDA retracted its EUA on June 15, 2020, warning not to use these agents to treat COVID-19 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The intravascular microaxial LVAD first entered the market via 510(k) clearance in 2008, based on being deemed “substantially equivalent” to prior cardiopulmonary bypass pumps . The 2016 21st Century Cures Act further accelerated the device approval process, and despite the increasing reliance on postmarket studies, the FDA has required few such studies for class III invasive devices …”
mentioning
confidence: 99%
“…The FDA also needs stronger mechanisms and more accessible and transparent postmarket surveillance of devices, including strengthening periodic updates and warnings to clinicians . A recent analysis of all high-risk cardiovascular devices (n = 71) approved between 2015 to 2019 found that only 38% of 68 postapproval studies mandated were completed at 4 years and that the postapproval studies were limited by delays, revisions, and terminations; lack of active control groups; and an emphasis on surrogate rather than clinical outcomes . More robust surveillance mechanisms should include strengthening the Manufacturer and User Facility Device Experience database for adverse events reporting and mandating public registries to monitor outcomes for all invasive cardiovascular devices entering the market.…”
mentioning
confidence: 99%